Geometric Analysis of the Subang Road Section Sta 0+000 – Sta 3+000, West Java Province - Jais, Fadel Rafi Assyahkaran Putra; Yasir, Yasrizal; Setiawan, Deni; Isradi, Muhammad; Dermawan, Widodo Budi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Integrated road infrastructure planning is an important factor in ensuring traffic safety, comfort, and smoothness. This study aims to evaluate and redesign the technical aspects of the ±3 km Subang Road section in Subang Regency, West Java Province, with a focus on road geometric planning, flexible pavement structures, and drainage systems. The research method used is a quantitative-descriptive approach based on primary data from field surveys and secondary data covering traffic data, subgrade conditions, and regional rainfall. The planning analysis refers to applicable national standards to ensure that technical and road user safety criteria are met. The evaluation results showed that the existing road conditions did not fully comply with the planning requirements, thus requiring adjustments to the horizontal and vertical alignment elements to be consistent with the planned speed. The redesign resulted in a geometric layout that improved stopping sight distance, vehicle stability, and driving comfort. The flexible pavement structure is designed based on the bearing capacity of the subgrade and projected traffic growth during the design life, so that it is expected to be able to withstand vehicle loads optimally and extend the service life of the road. In addition, the drainage system is designed to effectively drain rainwater runoff to prevent puddles and pavement damage. Overall, the results of the study show that the application of integrated road planning based on technical standards can improve road operational performance, reduce the potential for accidents, and support smooth mobility and economic growth in Subang Regency.